Subjective socioeconomic status causes aggression A test of the theory of social deprivation. [article]. - Greitemeyer, Tobias
Seven studies (overall N = 3690) addressed the relation between people's subjective socioeconomic status (SES) and their aggression levels. Based on relative deprivation theory, we proposed that people low in subjective SES would feel at a disadvantage, which in turn would elicit aggressive responses. In 3 correlational studies, subjective SES was negatively related to trait aggression. Importantly, this relation held when controlling for measures that are related to 1 or both subjective SES and trait aggression, such as the dark tetrad and the Big Five. Four experimental studies then demonstrated that participants in a low status condition were more aggressive than were participants in a high status condition. Compared with a medium-SES condition, participants of low subjective SES were more aggressive rather than participants of high subjective SES being less aggressive. Moreover, low SES increased aggressive behavior toward targets that were the source for participants' experience of disadvantage but also toward neutral targets. Sequential mediation analyses suggest that the experience of disadvantage underlies the effect of subjective SES on aggressive affect, whereas aggressive affect was the proximal determinant of aggressive behavior. Taken together, the present research found comprehensive support for key predictions derived from the theory of relative deprivation of how the perception of low SES is related to the person's judgments, emotional reactions, and actions. -- (from the authors)